The Effect of Semangat Juice (Watermelon Tomato) on Elderly Hypertension During The Covid-19 - Joyeti Darni; Retno Wahyuningsih; Lalu Khairul Abdi (Jurnal Gizi Prima (Prime Nutrition Journal), 2022)
Background. Many sufferers do not know if they have hypertension because they are often without complaints, so this disease is called the silent killer. However, hypertension is essential in therapy because it can cause complications in vital organs. Prevention and treatment of hypertension recommend lifestyle modifications such as increasing the intake of vegetables and fruit. Watermelon and tomatoes are fruits that are often found in NTB Province. The fruit can be used as an alternative prevention and treatment of hypertension. Research Methods. This research is a quasi-experimental type of research. The sample came from the UPTD Puskesmas Babakan, Mataram City, West Nusa Tenggara. The juice intervention was given for ten consecutive days, once per day, in the afternoon, as much as 200 ml from 200 g watermelon and 100 g tomatoes. The results were analyzed using paired t-test. Research Result. In the treatment group, the decrease in systolic blood pressure was 18.3 mmHg, and the reduction in diastolic was 11.4 mmHg.While the difference in the decline in the control group for systolic was 4.75 mmHg, and the diastolic level in the control group had an increase of 5.4 mmHg.  Conclusion. There is an effect of decreasing systolic and diastolic blood pressure after being given the spirit juice (watermelon) intervention.